Hard shell gas-filled contrast enhancement particles for colour Doppler ultrasound imaging of tumors() - Martinez, H. Paul (2010)
Hollow hard shell particles of 200 nm and 2 micron diameter with a 10 nm thick porous silica shell have been synthesized using polystyrene templates and a sol–gel process. The template ensures than the hollow particles are monodispersed, while the charged silica surface ensures that they remain suspended in solution for weeks. When filled with perfluorocarbon gas, the particles behave as an efficient contrast agent for colour Doppler ultrasound imaging in human breast tissue. The silica shell provides unique properties compared to conventional soft shell particles employed as ultrasound contrast agents: uniform size control, strong adsorption to tissue and cells immobilizing particles at the tissue injection site, a long imaging lifetime, and a silica surface that can be easily modified with biotargeting ligands or small molecules to adjust the surface charge and polarity.